The lexical field of the substantives of "gift" in ancient Hebrew - Zanella, Francesco (Studia Semitica Neerlandica, 2010)
This book provides an exhaustive analysis of the semantic domain of 'gift' in Ancient Hebrew. The investigation focuses on the single lexemes and provides an overall picture of the developments of the lexical field across the linguistic layers of Ancient Hebrew